Management of Henoch-Schonlein Purpura with Gastrointestinal Manifestations in Children - Wardhani, Rizki Luthfia; Saroh, Siti Ariffatus (Muhammadiyah Medical Journal, 2023)
Henoch-Schonlein Purpura (HSP) is systemic vasculitis in children, hallmark by inflammatory infiltration of polymonuclear leukocytes in small blood vessels, followed by IgA1 immune deposits. HSP prevalence is approximately 3-27 cases per 100,000 children. The inflammatory process in HSP causes an ischemia and hemorrhagic process characterized by non-thrombocytopenia purpura, arthralgia, gastrointestinal problems, and kidney impairment. This process is called leukocytoclastic vasculitis. A 10-year-old boy came to ER of Dr. Sayidiman Magetan Hospital presenting with diffuse abdominal pain and purpura skin lesions in body. The complaint started with a red rash on both legs, then progressively extended to both hands, thighs, and buttocks, and continued with severe abdominal discomfort, nausea, dizziness, fever, and the patient also experienced a brownish-black stool. The patient was diagnosed with Henoch-Schonlein purpura with gastrointestinal manifestations based on medical examination. The patient stayed for six days at the hospital, and the condition improved.